Adaptive Selective Predictive For Image Data Compression - Al-Khafaji, Ghadah (Iraqi Journal of Science, 2024)
In this paper, an adaptive selective predictive coding method is proposed forintraframe coding techniques. The adopted techniques overcome the complexityresidual ideal case (i.e., residual does not become random noise) where the residualstill suffers from the existence of redundancy. The suggested techniques attempt tosift over any redundancy embedded in the residual where the quality improves thanthat of traditional predictive coding, selective predictive coding and of fixedpredictor coding.